Analisis Penyebab Cacat Produk pada Proses Produksi Polyster dengan Metode Six Sigma - Yulizan Rizki; Imam Maulana Firdaus (Universitas Islam Raden Rahmat, Malang, 2024)
Along with current technological developments, national companies are encouraged to carry out updates and innovations in quality control, especially in producing high quality and high competitiveness. Quality control aims to achieve zero defect levels, including that carried out by PT. Argatha Jaya currently. This research aims to reduce the reject rate and determine priority problems in the polyester production process. This research uses the six sigma method based on a simple problem solving methodology consisting of Define, Measure, Analyze, Improve and Control. This method combines various statistical tools and other process improvement approaches. The results of this research show that the company's Sigma level in July 2020, which was carried out on the Polyster unit, obtained a value of 3.59. These results illustrate that quality control is not optimal and improving it requires prioritization with FMEA analysis which can detect failed products in a particular process